2019
DOI: 10.1021/acsami.9b17851
|View full text |Cite
|
Sign up to set email alerts
|

Facile Formation of 2D–3D Heterojunctions on Perovskite Thin Film Surfaces for Efficient Solar Cells

Abstract: The interfaces between perovskite and charge transport layers greatly impact the device efficiency and stability of perovskite solar cells (PSCs). Inserting an ultrathin wide-bandgap layer between perovskite and hole transport layers (HTLs) has recently been shown as an effective strategy to enhance device performance. Herein, a small amount of an organic halide salt, N,N′-dimethylethylene-1,2-diammonium iodide, is used to create two-dimensional (2D)−three-dimensional (3D) heterojunctions on MAPbI 3 thin film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 71 publications
0
45
0
Order By: Relevance
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Moreover, previously reported work indicated that trap states mainly located at the interfaces of multilayers of whole device (called interface defects) and at the perovskite surface (called surface defects), which are effectively related to the energy level matching, hysteresis, charge carriers dynamics, and the long‐term environmental and operational stability. [ 18–22 ] Therefore, it is indispensable to explore an impressive way to diminish the defects, particularly at the interfaces, for acquiring the high‐efficient and stable PSCs. Currently, there are lots of approaches to improve the performance and stability of PSCs, containing additive engineering, using additive into a perovskite absorber layer and interface engineering, modifying the hole transport layer (HTL)/perovskite or perovskite/electron transport layer (ETL) interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, nonstoichiometric ratio of PbI 2 in the perovskite film presented at the grain boundaries or on the surface can decrease charge recombination by the creation of I‐type band alignment. [ 27 ] Halide salts such as FACl, [ 28 ] 2D perovskite materials, for example, PEA 2 PbI 4 and N , N ′‐dimethylethylene‐1,2‐diammonium iodide, [ 18,29,30 ] wide bandgap perovskite material such as FAPbI 3− x Br x , [ 31 ] insulating polymers such as polystyrene, [ 32 ] organic halide salt such as phenethylammonium iodide, [ 17 ] and cetyltrimethylammonium bromide [ 33 ] have been utilized as the modifiers to neutralize the uncoordinated ions at the perovskite surface. Ionic liquids (ILs) are considered to be efficient passivation materials owing to their characteristics such as good heat resistance and ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] However, long-term stability is widely considered to be one of the major challenges that must be addressed before large scale com-mercialization of PSCs. [5,6] Many approaches have been developed during last few years in improving the stability of PSCs,i ncluding surface passivation of halide perovskite thin films using various types of materials,s uch as organic halide salts, [2,7,8] polymers, [9][10][11] organic small molecules, [5,[12][13][14] lowdimensional perovskite hybrids, [15,16] inorganic compounds, [17,18] and many others. [19,20] Thef unction of surface passivation is mainly twofold.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is anticipated that the 2D perovskite will be formed as an ultra-thin layer, as shown in Fig. 1c 25 . The SEM images of the perovskite films passivated by different concentrations of PDAI are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%